NGHIÊN CỨU LÝ THUYẾT SỰ TƯƠNG TÁC TẠO PHỨC GIỮA MONOHALOGEN CủA ETAN VỚI NƯỚC VÀ HIĐRO PEROXIT - Diệp, Phạm Ngọc; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
The complexes between monohalogenated ethanes C2H5X (X = H, F, Cl, Br) with water and hydrogen peroxide have been studied theoretically at both the MP2/6-311++G(d,p) and MP2/6-311++G(3df,2p) levels. The calculations were included the optimization of the geometries, the vibrational frequencies and IR intensities of the n(OH) and n(CH) vibrations along with a natural bond orbital (NBO) analysis. The complexes are formed by OH...X and CH...O hydrogen bonds. Blue shifts and red shifts are predicted for the n(CH) vibrations of the CH...O bonds and the í(OH) vibrations of the OH…X bonds respectively. The NBO parameters are also discussed.